Media influence on attitudes toward guns and gun control - Dowler, Kenneth (American journal of criminal justice, 2002)
This study employs the 1995 National Opinion Survey of Crime and Justice to examine the effect that media consumption (hours of television viewing per week, regular viewing of crime drama, and primary source of crime news) has on attitudes towards guns and gun control. Logistic regression results indicate that regular viewers of crime shows are more likely to oppose gun control and believe that firearms prevent crime. Respondents who receive their primary crime news from the print media are more likely to disagree with making it easier to conceal firearms. The author suggests that violent depiction of crime on television may influence viewers’ attitudes toward guns and gun control.